Giant monopole and quadrupole resonances in rotating nuclei - Åberg, Sven (Nuclear Physics, Section A, 1987)
Isoscalar and isovector giant monopole and quadrupole resonances built on high-spin states are studied in a simple model. Using the random-phase approximation the giant resonance states at spin zero are calculated in the deformed harmonic oscillator potential. Quadrupole and monopole operators, as well as the corresponding coupling constants, are obtained in a self-consistent way, and the coupling between them is properly taken into account. The influence of rotation is investigated by coupling the giant resonance phonons to an axially summetric rigid rotor. Energy splitting into four main components due to quadrupole deformation, and into six main components due to rotation is studied. Decay properties in terms of quadrupole and monopole radiation from giant resonances in rapidly rotating nuclei are examined. Special attention is paid to the possibility of building giant resonances on superdeformed high-spin states. At the 2:1 deformation we predict the main part of the monopole strength in the K = 0 component of the giant quadrupole resonance, situated at a centroid energy of 39A- 1 3 MeV and 91A- 1 3 MeV for the isoscalar and isovector giant resonances, respectively.